(untitled) (Physical Education, Health and Social Sciences, 2025)
Maternal health is a serious global concern, with maternal mortality and morbidity remaining major challenges in various countries. It includes the health and well-being of women for the duration of pregnancy, childbirth, and the post-delivery period. In spite of global struggles, countries with less healthcare resources continue to experience disproportionately great risks to maternal health. In Pakistan, the condition and situation is predominantly concerning, as many regions, particularly Balochistan, are cope with inadequate healthcare infrastructure, cultural barricades, and socioeconomic issues. This study examines the perceptions of health practitioners regarding maternal health challenges in the District of Killa Saifullah, Balochistan. A purposive sampling technique was used to recruit 12 healthcare professionals from the District. The results elaborate numerous serious barricades to maternal health, including an absence of antenatal care services, inadequate medical workforce, nutrient deficiencies, and a deficiency of awareness among the people. In addition, cultural perception such as fleeing from ultrasound in fear of its application under Islamic culture and the prohibition of seeking medical treatment due to similar reasons exacerbates the situation. The study found lack of access to important clinical equipment like laboratories and ultrasound machines, as well as shortage of drugs. The consequences of maternal health are significantly impeded by low levels of education, socio-economic disparities and low accessibility to healthcare facilitation. This paper provides insights to improve maternal health in the District Killa Saifullah, Balochistan by eliminating these barriers that appear to have required quality in education, greater accessibility to the healthcare structure and culturally tailored counseling.